THE FACTORS DETERMINING ENTREPRENEURSHIP TRENDS IN FEMALE UNIVERSITY STUDENTS: SAMPLE OF CANAKKALE ONSEKIZ MART UNIVERSITY BIGA FACULTY OF ECONOMICS AND ADMINISTRATIVE SCIENCES1, (part 2) - Yelkikalan, Nazan; Yuzuak, Elif (European Scientific Journal, ESJ, 2014)
Nowadays, importance of entrepreneurship increases as the event of economic developments and changes. Therefore, entrepreneurs are needed for achieving global or regional improvement. Entrepreneur is a person who realizes a gap in the economy, effectuates his/her creative ideas and closes this gap. Individuals intend in the direction of to be entrepreneur through they are affected by personal characteristics, society, gender and their educations. Universities that integrated changes and transformations let their students’ entrepreneurial intention by entrepreneurship education. Nowadays, universities that attempt with limitless source of information inside and outside association, have to coach students who join to the regressive economy as a good entrepreneur. Entrepreneurial education in the universities leads young’s who want to employ by oneself and to make new job opportunities with creative ideas. Female students who receive certain pressures and discriminations in the social and business life are to become conscious and to increase their self-confidence through having education. In this way, they will keep entrepreneurship idea warm and intend to be entrepreneur. The purpose of study is to research factors that effect entrepreneurial intention of female students in university. In this context, a survey was conduct for determining effect of entrepreneurship education on entrepreneurial intentions of female students with Perceived behavioral control, Subjective norms , Personal attitude as three dimensions. In result of research, it was reason out entrepreneurship education, parents’ education level and entrepreneur in family effect on entrepreneurial intentions. Besides, it was reason out entrepreneurship education effects on Perceived behavioral control, Subjective norms ,Personal attitude that are entrepreneurial intention factors. Each individual has tendency towards different professions as a result of his/her personality traits, the family s/he has grown in, the culture of the society s/he lives in, and the education s/he has received. Moreover, all these factors lead to differences in terms of gender. Within this context, female students enrolled in universities that offer professional and academic education may have entrepreneurial intentions generated by the entrepreneurship education they have received.